Analisa Pemakaian IPv6 di Indonesia - Daniel Satriautama; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2015)
The development of the Internet has been growing rapidly. Almost all mobile devices using the internet as a means of communication. The Internet addressing which is still widely used is based Internet Protocol version 4 (IPv4). Since version 4 has almost run out of addresses it is time to change to Internet Protocol version 6 (IPv6). Also in 2015 Internet Protocol version 6 (IPv6) began to be held globally, thus making each country must prepare to implement these changes.This analysis aims to show information about Internet Protocol version 6 (IPv6) in Indonesia ranging from information Domain Name Server (DNS), Mail Server, Web site-based addressing and the use of version 6 in Indonesia. This analysis also provides an update in the form of graphs. This analysis also compares results obtained with data from internet. This research also shows charts about development of version 6 addressing from the year 2010 up to March 2015.Based on test results, the results of this analysis is shown in the form of a website which is divided into 3 parts, i.e. Domain Name Server (DNS), Mail Server, Web site. The features of this Website are a list of hosts that use version 6, analysis graphs to a company this list, charts the development of IPv6 chart, automatic ping when the website is opened. Tthere is a website for admins to make it easier to perform the update when needed